Cancer-Related Cognitive Impairment in Breast Cancer Patients: Influences of Psychological Variables - Yesol Yang; Cristina C Hendrix (Elsevier, 2018)
Approximately 3.1 million women in the US are living with breast cancer and up to 75% of these women experience cancer-related cognitive impairment (CRCI). CRCI is described as impairments in memory, verbal fluency, thought processes, and attention span. Despite the high prevalence of breast cancer, only a few studies have been published on CRCI and most of these studies primarily focused on its pathophysiological mechanism. However, recent evidence has demonstrated that breast cancer patients with CRCI are more likely to have high level of psychologic distress, suggesting a possible relationship between CRCI and psychologic distress. This review aims to examine existing literature that describes CRCI in relation to psychological distress among breast cancer patients. One thousand four hundred and ninety-eight articles were searched using PubMed, CINAHL, and PsycINFO. Thirteen studies met inclusion criteria, and one article was additionally pulled from article reference lists. Of these19 studies, psychologic distress has been operationalized in varied ways such as anxiety (n = 3), depression (n = 2), both anxiety and depression (n = 4), stress (n = 4), worry (n = 2), mental fatigue (n = 1), and undefined psychological distress (n = 2). Except for six studies designed as a longitudinal study, the rest of studies used a cross-sectional design. Twelve studies used both subjective and objective measures to assess cognitive function. We found that the patients with high psychological distress displayed lower performance on cognitive function tests. Our finding indicates that psychological variables contributed to CRCI that breast cancer patients experienced. Areas for further investigation are proposed that will advance the care of breast cancer patients with CRCI.